Uterine artery pseudoaneurysm and embolisation during pregnancy - Roeckner, Jared T (BMJ Case Rep, 2020)
Uterine artery pseudoaneurysm in pregnancy is a dangerous condition as rupture can be catastrophic due to the large volume of uterine blood flow. We present a case of a healthy, young woman with a desired pregnancy at 15 weeks of gestation incidentally discovered to have a pseudoaneurysm of the uterine artery during a routine prenatal ultrasound. She underwent initial thrombin injection followed by endovascular coil embolisation of the left uterine artery and carried the pregnancy to term without further complications.